Implementation of scroll compressors into the Cordier diagram. (August 2019) - Thomas, C; Margraf, M; Stoeckel, C; Klotsche, K; Hesse, U
Abstract: Selecting the most suitable machine type for a specific compression task is an essential step to ensure a reliable and economical operation of the overall system. For this, the eligibility of a compression principle can be estimated by the enhanced Cordier diagram by Grabow based on only a few input parameters (specific isentropic work, flow rate, speed and characteristic diameter). The working principle of scroll machines is known for more than one century. However, only the improvements in manufacturing processes during the last decades allowed their utilisation and a significantly increasing interest in scrolls in more and more fields of applications can be seen. Unfortunately, the scroll machine has not yet been introduced to the Cordier diagram. Therefore, this paper shows a method for determining the characteristic key figures for different given scroll geometries. Based on this, it is shown how to implement scroll compressors into the Cordier diagram, i.e. different designs are analysed and the resulting data points are introduced to the diagram.